Fumonisin affects performance and modulates the gene expression of IGF-1 and GHR in Nile tilapia fingerlings and juveniles - Claudino da Silva, Stefania Caroline; Lala, Bruno [UNESP]; Carniatto, Caio Henrique de Oliveira; Schamber, Christiano Rodrigues; Nascimento, Carlos Souza; Braccini, Graciela Lucca; Porto, Carla; Roldi, Gabriel; Tanamati, Fernanda; Gasparino, Eliane (Elsevier, 2019)
Fumonisins (FB) are mycotoxins produced during secondary metabolism of Fusarium verticillioides and Fusarium proliferatum fungi and can prevent animal performance. In this study, the hypothesis that fumonisin affects the expression of IGF-1 and GHR genes in Nile tilapia (Oreochromis niloticus) fingerlings and juveniles was tested. Nile tilapia fingerlings and juveniles received diets with and without the inclusion of fumonisin (50 mg FB kg−1 of feed) to evaluate their effects on weight gain (WG), feed intake (FI), feed conversion (FC) and mRNA expression of GHR and IGF-1 in the liver. The fumonisin-free diet was used as a control treatment. All variables were evaluated after 20 days of treatment. The diet containing 50 mg FB kg−1 of feed significantly reduced WG (P < 0.0001) and worsened FC (P < 0.0001) for fingerlings, but did not affect FI. For juveniles, the inclusion of fumonisin did not affect FI, FC and WG. GHR and IGF-1 mRNA expression of both fingerlings and juveniles was significantly reduced by the inclusion of fumonisin (P < 0.0001). These results indicate that fumonisin affects the hepatic expression of GHR and IGF-1 in Nile tilapia, but the phenotypic effect is more evident in fingerlings.
Keywords: Feed conversion; Oreochromis niloticus; Performance; Weight gain